Penerapan Kompensasi Perjanjian Kerja Waktu Tertentu (Pkwt) di PT. Flobamora Bravo Indonesia - Safitri, Elsa Nur (Peneliti.net, 2025)
Fixed Term Employment Agreement (PKWT) Compensation is one of the government's efforts to protect workers/laborers as regulated in Article 61A of Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law, the article requires employers to provide compensation to workers/laborers when the fixed term employment agreement ends. In its implementation in the field, of course, there are many violations committed by employers that are not in accordance with existing regulations. One of them is at PT. Fobamora Bravo Indonesia, where 106 PKWT workers/laborers did not receive PKWT compensation starting from the ratification and enactment of the regulations regarding PKWT compensation until now. The purpose of the research that will be discussed in this thesis is the implementation of Fixed Term Employment Agreement (PKWT) compensation at PT. Flobamora Bravo Indonesia which does not implement compensation and the obstacles that affect the implementation of Fixed Term Employment Agreement (PKWT) compensation at PT. Flobamora Bravo Indonesia. This type of research is sociology, because in this study the author conducted direct research at the location or place to be studied in order to provide a complete and clear picture of the problem being studied. This research was conducted at PT. Flobamora Bravo Indonesia, while the population and sample are all parties related to the problem studied in this study, namely the HRD Manager of PT. Flobamora Bravo Indonesia, Workers/Laborers at PT. Flobamora Bravo Indonesia. The sources in this study were Civil Servants of the Manpower Office in the Industrial Relations Division of Riau Province. The data sources used were primary data, secondary data and tertiary data, and data collection techniques in this study were interviews, questionnaires and literature studies. The results of this study can be concluded that the implementation of compensation for Fixed-Term Employment Agreements (PKWT) at PT. Flobamora Bravo Indonesia was not carried out as regulated in the laws and regulations. This is due to obstacles in its implementation, including the unavailability of funds owned by PT. Flobamora Bravo Indonesia, lack of knowledge of PKWT workers/laborers regarding their rights, lack of compliance of PT. Flobamora Bravo Indonesia to the law, lack of supervision from the Riau Province Manpower and Transmigration Office, to overcome this problem, the author suggests that PT. Flobamora Bravo Indonesia pay PKWT compensation, and it is expected that PKWT workers will seek information about PKWT compensation, and the Riau Province Manpower and Transmigration Office can conduct socialization about PKWT compensation to PKWT Workers.